The Evolution of Mortgage Legislation and the Role of the Banking Industry in Kuwait - Al-Hasawi, Hamad (The Arab Journal of Administration, 2025)
The housing sector plays a crucial role in the overall economic development of any society. It holds a significant share in the national economy and its importance is further highlighted by the positive external effects it generates. Additionally, the spillover effects of the housing sector contribute to the growth of other economic sectors. This sector is intricately linked to the land market, commodity markets (especially durable goods), and the labor market. Moreover, it has implications for the social and political climate, as well as other critical issues. In developing countries, housing expenditure often constitutes a substantial portion of household spending. Due to its long-term nature, housing expenses continue to be a financial burden on individuals throughout their lives. For many families, housing represents their largest asset. Despite the significant activity in Kuwait’s real estate sector, there has yet to be a mortgage law enacted to address and streamline the requirements for borrowers seeking residential property. This research paper is therefore, calling for the establishment of a mortgage sector in Kuwait which is crucial to cater to the housing demand of segments of the population who may not opt for government housing, face delays in accessing it, or find government loans insufficient for financing suitable housing options.